Experimental Study on Gas Flow in a Rough Microchannel - Li, Deming; Yang, Ruixue; Cao, Hui; Yao, Feng; Shen, Chaoqun; Zhang, Chengbin; Wu, Suchen (Frontiers in Energy Research, 2022)
The shape and relative roughness of a rough surface have an important influence on microscale flow and heat transfer. In this study, a rectangular silicon microchannel (0.8 mm width and 11.9 μm height) with a large width-depth ratio is fabricated by the MEMS micromachining process. The silicon surface of the microchannel and the two-dimensional rough contours of the glass surface are measured, and the fractal dimensions taken as the only quantitative parameter of the surface morphology are calculated. The three-dimensional morphology of the silicon surface is measured by a confocal laser microscope and atomic force microscope. On this basis, a microscale gas flow performance test system is designed and built, and the flow characteristics of nitrogen and helium in rough silicon microchannel are experimentally studied. The experimental results show that the rough profiles of the silicon surface and the glass surface have possessed self-affine characteristics. Both nitrogen and helium show a certain degree of boundary slip when they flow in a microchannel. The degree of slip of helium flow is larger than that of nitrogen flow, which verifies the rarefied effect of microscale gas flow.